Transcriptomics profiling of human PSC cultured under different conditions - Falk, Anna (Karolinska Institutet, 2025)
This study has used transcriptome data derived for quality testing of pluripotent stem cells to investigate how different culture conditions affect gene expression. All pluripotent stem cells in the study have passed pluritest testing.
Data contains transcriptomics signatures of pluripotent stem cell lines originating from human donors, measured with Illumina Gene Expression HT12 Direct Hybridization assay (Illumina HT 12v.4). Human induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs) were cultured under either undefined culture conditions or defined and xenofree culture conditions, or transferred from the undefined to defined condition. These are labeled as feeder, laminin and transfer in the sample table, respectively. Skin biopsy samples were collected with informed consent from donors for creating models for studying human development. Donor samples were reprogrammed to iPSC and transcriptome analyses were performed for quality testing of the pluripotent cells.

The dataset consists of 115 files in IDAT format and one in CSV format.
The total size of the dataset is approximately 335 MB.

Den här studien har använt transkkriptomikdata från kvalitetstestning av pluripotenta stamceller för att undersöka hur olika odlingsförhållanden påverkar genuttryck. Alla pluripotenta stamceller i studien har klarat test av pluripotens.
Data innehåller transkriptomiska signaturer av pluripotenta stamcell-linjer från humana donatorer, uppmätta med Illumina Gene Expression HT12 Direct Hybridization assay (Illumina HT 12v.4). Humana inducerade pluripotenta stamceller (iPSC) och embryonala stamceller (ESC) odlades under antingen odefinierad eller definierad och xenofri kultur, eller överförd från odefinierade till definierade kultur. Dessa benämns som feeder, laminin och transfer tabellen över proverna, respektive. Hudbiopsier samlades in efter samtycke från donatorer för modellering av tidig human utveckling. Donatorproverna omprogrammerades till iPCS och transkriptomanalyser utfördes för att kvalitetstesta de pluripotenta stamcellerna.

Datasetet består av 115 filer i IDAT-format och en i CSV-format.
Datasetets totala storlek är ungefär 335 MB.
Transkriptomikdata på humana PSC odlade under olika förhållanden
Keywords: Gene Expression; Genuttryck; Calcium Signaling; Kalciumsignalering; Pluripotent Stem Cells; Pluripotenta stamceller; cell culture; cellodling; stem cells; stamceller; gene expression; genuttryck; pluripotent stem cells; pluripotenta stamceller; calcium signalling; kalciumsignalering; Medical Biotechnology (Focus on Cell Biology, (incl. Stem Cell Biology), Molecular Biology, Microbiology, Biochemistry or Biopharmacy); Medicinsk bioteknologi (inriktn. mot cellbiologi (inkl. stamcellsbiologi), molekylärbiologi, mikrobiologi, biokemi eller biofarmaci); Evolution and Developmental Genetics; Evolution och utvecklingsgenetik